2001
DOI: 10.1034/j.1399-0039.2001.057002118.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA genes in Macedonians and the sub-Saharan origin of the Greeks

Abstract: HLA alleles have been determined in individuals from the Republic of Macedonia by DNA typing and sequencing. HLA-A, -B, -DR, -DQ allele frequencies and extended haplotypes have been for the first time determined and the results compared to those of other Mediterraneans, particularly with their neighbouring Greeks. Genetic distances, neighbor-joining dendrograms and correspondence analysis have been performed. The following conclusions have been reached: 1) Macedonians belong to the "older" Mediterranean substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
73
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 14 publications
15
73
4
Order By: Relevance
“…These haplotypes has not been detected in the healthy Macedonian population, but there is no statistically signifi cant association, probabely because of the small number of investigated persons with autism. The most common alleles in control group were: A*01-C*07-B*08-DRB1*03 (3.1 %), A*02-C*07-B*18-DRB1*11 (2.0 %), A*02-C*06-B*13-DRB1*07 (1.5 %), A*11-C*12-B*52-DRB1*16 (1.5 %), which is different to the other Macedonian antropological study (19). They found increased frequencies of A*02-B*51-DRB1*1601 (3.2 %), and A*03-B*18-DRB1*1601 (2.6 %) (19).…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…These haplotypes has not been detected in the healthy Macedonian population, but there is no statistically signifi cant association, probabely because of the small number of investigated persons with autism. The most common alleles in control group were: A*01-C*07-B*08-DRB1*03 (3.1 %), A*02-C*07-B*18-DRB1*11 (2.0 %), A*02-C*06-B*13-DRB1*07 (1.5 %), A*11-C*12-B*52-DRB1*16 (1.5 %), which is different to the other Macedonian antropological study (19). They found increased frequencies of A*02-B*51-DRB1*1601 (3.2 %), and A*03-B*18-DRB1*1601 (2.6 %) (19).…”
Section: Discussioncontrasting
confidence: 39%
“…The most common alleles in control group were: A*01-C*07-B*08-DRB1*03 (3.1 %), A*02-C*07-B*18-DRB1*11 (2.0 %), A*02-C*06-B*13-DRB1*07 (1.5 %), A*11-C*12-B*52-DRB1*16 (1.5 %), which is different to the other Macedonian antropological study (19). They found increased frequencies of A*02-B*51-DRB1*1601 (3.2 %), and A*03-B*18-DRB1*1601 (2.6 %) (19). None of our patients carried alleles or haplotype, which are protective for autism in our population.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…If autism is in some cases the result of immune system attack, then particular HLA antigens might be involved as a sufficient or predisposing factor [30]. The immunogenetic profile of the Macedonian population represented by HLA genes is published for HLA-A, -B, -DR, -DQ allele frequencies [31], for HLA-DRB1, DRB3/4/5 and DQB1 polymorphism [32], for HLA-A and HLA-B epidemiology [33], for high-resolution sequence-based method for direct HLA-DRB1 typing [34], for ambiguous allele combinations at the allele group level of HLA-A, -C and -B loci [35], and for HLA-DQB1 typing [36]. Our results showed significantly increased frequencies of HLA-C*03 and HLA-DRB1*01 alleles in autistic patients when compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that HLA-A*02,HLA-B*51, and HLA-DRB1*11 are the most frequent HLA alleles in unrelated Turkish individuals. 8 According to the literature, HLA-A*02, HLA-B*51, and HLA-DRB1*11 are found in Armenians and HLA-A( * )02, HLA-B( * )35, and HLA-DRB1( * )11 are found in Brazilian renal transplant candidates. 9,10 When we look at the PRA positivity, we found that A02, A68, A23, B49, B37, B7, DR7, DR14, DR11, DQ9, DQ8, and DQ2 were the most common anti-HLA antibodies.…”
Section: Bilkay Baştürk Et Al/experimental and Clinical Transplantatimentioning
confidence: 99%